Kidney injury molecule type-1, interleukin-18, and insulin-like growth factor binding protein 7 levels in urine to predict acute kidney injury in pediatric sepsis - Ganda, Idham Jaya; Kasri, Yusriwanti; Susanti, Maya; Hamzah, Fitrayani; Rauf, Syarifuddin; Albar, Husein; Aras, Jusli; Fikri, Bahrul; Lawang, Sitti Aizah; Daud, Dasril; Laompo, Amiruddin; Massi, Muhammad Nasrum (Frontiers in Pediatrics, 2022)
Background This study aimed to observe the role of urinary kidney injury molecule (KIM-1), interleukin (IL-18), and insulin-like growth factor-binding protein 7 (IGFBP-7) levels in predicting acute kidney injury (AKI) in children with sepsis. Material and Methods This prospective cohort observational study was conducted at Dr. RSUP. Wahidin Sudirohusodo, Makassar, South Sulawesi, from January to December 2021. Inclusion criteria were septic patients treated in the pediatric intensive care unit (PICU) aged 1 month to 18 years with normal serum creatinine or normal urine output (>5 ml/kg/body weight (BW)/h in 6–12 h). Patients with a history of kidney disease, prior urinary tract infection, or history of using nephrotoxic drugs were excluded. Results There was a significant difference in urinary KIM-1, IL-18, and IGFBP-7 levels between septic patients with and without AKI. The cut-off point for urinary KIM-1 level in sepsis with and without AKI was 1.666 ng/ml, with sensitivity of 82.5%, specificity of 82.2%, and a relative risk (RR) [95% confidence interval (CI)] of 6.866 (95% CI, 3.329–14.165). The cut-off point for urinary IL-18 levels was 3.868 ng/ml, with sensitivity of 92.50%, specificity of 91.78%, and RR of 20.078 (95%CI, 6.593–61.142). The cut-off point for urinary IGFBP-7 levels was ≥0.906 ng/ml with a sensitivity of 75.00%, specificity of 75.34%, and RR of 4.063 (95% CI, 2.206–7.483). Conclusion Urinary KIM-1, IL-8, and IGFBP-7 levels could be used to predict AKI in septic patients. Urinary IL-8 has a higher sensitivity and specificity as a predictor of AKI in patients with sepsis.